1998
DOI: 10.1300/j074v10n03_04
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Employment and Serious Illness on Grandmothers Who Are Raising Their Grandchildren

Abstract: Increasing numbers of children are living in families consisting of grandparents and grandchildren. This paper presents findings of a study in which 123 caregiving grandmothers were interviewed. Fifty-eight percent of these grandmothers were "career caregivers," whose homes were always filled with a child or grandchild. Most of them were in good to excellent physical health and their mental health was at least as good as that of a national sample. Regression analyses found that having a life-threatening physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 16 publications
3
28
0
Order By: Relevance
“…Sands and Goldberg-Glenn (1998) reported a buffering effect of work on the caregiving stress faced by grandmother caregivers in the form of psychophysiological symptoms. Their finding is congruent with the literature suggesting that employed women caregivers are more likely to report higher self-esteem and life satisfaction than those who are unemployed (Moen, Robinson, & Fields, 1994).…”
Section: Background and Contextmentioning
confidence: 99%
“…Sands and Goldberg-Glenn (1998) reported a buffering effect of work on the caregiving stress faced by grandmother caregivers in the form of psychophysiological symptoms. Their finding is congruent with the literature suggesting that employed women caregivers are more likely to report higher self-esteem and life satisfaction than those who are unemployed (Moen, Robinson, & Fields, 1994).…”
Section: Background and Contextmentioning
confidence: 99%
“…The background characteristics examined in this study, identified in earlier research as impacting caregiving stress, include gender (Fredriksen, 1996a;Kramer & Kipnis, 1995), race and ethnicity (Fredman, Daly, & Lazur, 1995;Hinton, Fox & Levkoff, 1999), job classification (Fredriksen & Scharlach, 1997), age (Scharlach & Fredriksen, 1994) and health status (Cochrane, Goering & Rogers, 1997;Pavalko & Woodbury, 2000;Sands & Goldberg, 1998).…”
Section: Conceptual Modelmentioning
confidence: 99%
“…Although we could find no other studies that estimated the association between probable depression and IOF, studies focused on parents of children with chronic or life-limiting illnesses have found these parents have greater levels of stress, posttraumatic stress disorder (PTSD), anxiety, and fear. [17][18][19][20] Hopia et al 21 notes that when a child has a serious illness oftentimes the whole family is ''ill'' and the overall health of the family becomes vulnerable. Pediatric palliative care programs, as opposed to other models of care, are designed to treat the family and not just the child.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that underemployment or unemployment is associated with greater levels of stress for parents of children with life-limiting and chronic conditions. 19,20 Further testing should be conducted to determine if the factors that affect impact on family are different for a broader socioeconomic group. Third, our study did not capture if the respondent was the child's mother or father.…”
Section: Discussionmentioning
confidence: 99%